Progress and prospects of oil and gas production engineering technology in China - Xinquan ZHENG; Junfeng SHI; Gang CAO; Nengyu YANG; Mingyue CUI; Deli JIA; He LIU (Petroleum Exploration and Development, 2022)
This paper summarizes the important progress in the field of oil and gas production engineering during the “Thirteenth Five-Year Plan” period of China, analyzes the challenges faced by the current oil and gas production engineering in terms of technological adaptability, digital construction, energy-saving and emission reduction, and points out the future development direction. During the “Thirteenth Five-Year Plan” period, series of important progresses have been made in five major technologies, including separated-layer injection, artificial lift, reservoir stimulation, gas well de-watering, and workover, which provide key technical support for continuous potential tapping of mature oilfields and profitable production of new oilfields. Under the current complex international political and economic situation, oil and gas production engineering is facing severe challenges in three aspects: technical difficulty increases in oil and gas production, insignificant improvements in digital transformation, and lack of core technical support for energy-saving and emission reduction. This paper establishes three major strategic directions and implementation paths, including oil stabilization and gas enhancement, digital transformation, and green and low-carbon development. Five key research areas are listed including fine separated-layer injection technology, high efficiency artificial lift technology, fine reservoir stimulation technology, long term gas well de-watering technology and intelligent workover technology, so as to provide engineering technical support for the transformation, upgrading and high-quality development of China’s oil and gas industry.